Konsep Spiritual dalam Serat Wirid Hidayat Jati Ronggowarsito - Fitri, Ach. (Postgraduate Studies UIN Sunan Ampel Surabaya, 2023)
This research is motivated by the growing concern over the decline of spiritual quality in modern society, which tends to be trapped in rationality and materialism, thus losing direction in attaining the perfection of the insān kāmil (the complete human). In this context, revitalizing the ethical and spiritual values of Javanese Islam becomes essential. One prominent figure offering a solution to this spiritual crisis is Raden Ngabehi Ronggowarsito through his work Serat Wirid Hidayat Jati. This text presents a profound perspective on the purification of the soul and the perfection of humanity through spiritual practice rooted in Islamic teachings and Javanese wisdom. The study employs a descriptive-analytical method combined with philological and hermeneutic approaches to explore the ethical, spiritual, and theological values embedded in the text. The findings reveal that Serat Wirid Hidayat Jati offers an integrative model between Islam and Javanese culture, emphasizing harmony between the outer and inner dimensions of human existence. This study contributes new insight into understanding Javanese Islamic ethics as a foundation for cultivating modern spiritual consciousness.